Financial Performance and Diversity on Boards of Directors in Brazil - Emiko Yoshinaga, Claudia; Heidemann Freitas, Taís; Andrey de Almeida Lopes Fernandes, Gustavo (Review of Business Management, 2025)
Purpose – This study investigates how different dimensions of board diversity influence the financial performance of non-financial Brazilian companies, focusing on Brazil’s institutional and cultural specificities. Theoretical framework – The theoretical framework combines Resource Dependence Theory (RDT), Agency Theory, and Upper Echelons Theory, emphasizing mechanisms through which board diversity may affect organizational performance. Design/methodology/approach – This is an empirical, longitudinal study analyzing data from 367 companies listed on B3 between 2011 and 2021. Panel data regression models with fixed effects were applied, with diversity variables constructed from indices such as Blau's, in addition to dummy variables. Findings – The results indicate statistically significant associations between some dimensions of diversity and financial performance, highlighting the positive impact of academic background diversity and previous board experience, as well as negative effects associated with female participation and positive effects from family ties. Research Practical & Social implications – This research offers important recommendations for improving governance practices in Brazil, suggesting that diversity should be promoted strategically and effectively, overcoming tokenism and aligning with national contextual specificities. Originality/value – The study contributes to the literature by conducting a comprehensive analysis of board diversity in Brazil, incorporating multiple dimensions beyond gender, such as academic background, experience, independence, and family ties, based on an unprecedented dataset for the country.